The Role of the (In)visible and the Secret in the Translation of Harryette Mullen s Muse & Drudge - Amorim, Lauro Maia [UNESP] (My University, 2011)
This paper, based on Jacques Derrida’s thoughts in Des Tours of Babel, addresses the issue regarding the (in)visible in translation, by arguing that the latter, beyond the traditional conception of communication, produces a complex set of relations between the visible and the invisible, which highlights the values of the non-dit and the secret that take place in their relation to interpretation. This line of thought underpins the discussion of my translation of two poems from Muse & Drudge (1995), by the African-American poet Harryette Mullen, whose dense poetry displays un(expected) possibilities of meanings and associations that proliferate in translation. It is argued that every act of translation entails a relationship between that which is translated (and made visible or intelligible through this act) and that which remains invisible and secret by resisting a definitive translation, which, as such, requires further interpretations in search for intelligibility (or “visibility”). We analyze the extent to which such relation between the visible and the invisible takes part in the translation of the notion of blackness raised by Mullen’s poems and how her translated poetry dialogues with issues of reception in Brazilian culture.
Keywords: literatura afroamericana; tradução e poéticas da identidade